Organization of Joint Laboratory Studies during Sanitary and Epidemiological Interventions in the Republic of the Congo by Rospotrebnadzor Specialists - S. A. Portenko; E. V. Naidenova; D. A. Agafonov; D. A. Kuznetsova; A. V. Evteev; A. A. Tushinsky; L. N. Dmitrieva; A. D. Katyshev; V. E. Kuklev; N. Obissa; V. Mabiala; J. Loubano; et al. (Проблемы особо опасных инфекций, 2024)
The study presents the data on organization of laboratory testing of clinical and environmental samples within the framework of establishing the etiology of the acute intestinal infections outbreak, performed by the specialists of the joint SAET of the Rospotrebnadzor in Dolisie (Republic of the Congo) in the period of 07–24 July, 2023.Materials and methods. In order to identify the causative agents of cholera and other acute intestinal infections of bacterial and viral nature, 177 clinical and environmental samples were tested, as well as cultures on solid nutrient media and bacterial suspensions. A total of 1023 tests were carried out by polymerase chain reaction (PCR) and 305 – using bacteriological method.Results and discussion. The causative agent of cholera has not been detected in any of the samples tested. Using the PCR method, markers of acute intestinal diseases agents (Salmonella spp., Shigella spp., Campylobacter spp., Rotavirus A) have been identified in 23 clinical samples and 1 sample of bacterial suspension. No DNA/RNA of pathogens has been detected in environmental samples. During culture studies, Salmonella enterica serovar Typhi have been isolated from 8 clinical samples, and their antibiotic sensitivity has been determined. Applying whole-genome nanopore sequencing, using the MinIon platform (Oxford Nanopore Technologies, UK), nucleotide sequences of 4 S. Typhi isolates have been investigated and deposited in the international database NCBI GenBank (No. CP141260, CP141193, CP141194, CP141195). Additionally, the analysis of initially sterile samples (blood, peritoneal fluid, intraoperational samples) from the patients of General and Reference hospitals of Dolisie has resulted in the identification of 5 cultures of non-fermenting bacteria, and their antibiotic sensitivity has been determined.